The Changes in Vitamins Content in Foods Soaked in the Chlorine Dioxide Solution - IMAEDA, KAZUO; YOSHIMURA, YOSHIHIRO; OHTANI, YOSHIKI; UCHIYAMA, KATSUMI; WATANABE, TAKAHO; CHEN, SHUMING; LIN, CHANGQING; TAMURA, KOHEI; OHSAWA, KEIKO (Eisei kagaku, 1991)
Twelve sorts of foods were tested to investigate the changes in the contents of ascorbic acid, vitamin B1 and vitamin B2 by soaking in 0.5 ppm chlorine dioxide solution. These vitamins in food were extracted with ultrasonic generator for 30 min, and the percentages of the loss of ascorbic acid, vitamin B1 and vitamin B2 were determined by the dichlorphenolindophenol method, thiochrome fluorescence method and lumifulavin method, respectively. It was found that there were the loss of 0-5% in the contents of vitamins after soaking for 15 min and 15-30% after 60 min. However, the percentage of the loss induced by the chlorine dioxide solution was less than that induced by 0.5 ppm chlorite, 0.5 ppm hypochlorite and potable water. The existence of Fe3+, Cu2+ in the solution had an obvious effect which accelerates the decomposition of ascorbic acid.